The Use of Dexmedetomidine on Pediatrics Undergoing Magnetic Resonance Imaging (MRI) Examination - Gembong Pandhu Suprobo; Karmini Yupono; Rudy Vitraludyono (Journal of Anaesthesia and Pain, 2021)
Dexmedetomidine, an α2 adrenergic agonist, has been commonly used as an off-label anesthetic adjuvant in various procedures and age groups. Lately, dexmedetomidine is increasingly preferred as sedation for pediatric patients undergoing MRI, which requires the patient to remain still in a deep sedation without disturbing airway patency. Dexmedetomidine administration via intranasal or buccal route is preferred for pediatric patients. Dexmedetomidine does not undergo significant pharmacokinetic changes when used in conjunction with other anesthetics, and has a good safety profile. It is 8-10 times more selective against α2 receptors than clonidine and produces sedation, analgesia, vasodilation, and bradycardia without significant airway and respiratory depression risk. Unlike other anesthetic agents, dexmedetomidine does not have any negative effect on brain development. Compared with propofol, dexmedetomidine has a longer onset and duration of action. Thus, dexmedetomidine can be used as the sole sedating agent in infants and children undergoing MRI procedures, with good sedation results and minimal side effects. However, correct dosing is very important given the side effects of bradycardia and hypotension that can occur with its use.